Resiliensi pada Dewasa Awal Pasca Kematian Saudara Kandung - Abigael Victoria Noya; Wahyuni Kristinawati (Institut Nalanda, 2026)
This study aimed to explore the dynamics of resilience in emerging adults following the death of a sibling. Loss during this developmental stage can trigger profound psychological disruption and the loss of a crucial emotional figure. The study employed a qualitative method with a phenomenological approach, involving three participants, two males and one female, aged 22–24 years, selected through purposive sampling. Data were collected through face-to-face in-depth interviews recorded with a voice recorder with participants’ consent. The resulting verbatim transcripts were analyzed using categorization techniques, including open coding, theme grouping, and meaning-making, and were validated through member checking. The findings indicate that resilience is not a linear process, but rather a dynamic movement from acute emotional crisis toward meaning-making, adjustment, and acceptance. In the initial phase of loss, participants generally experienced anger, emotional emptiness, reduced self-control, and uncertainty about their ability to endure. Resilience then developed through spiritual, cultural, and rational meaning-making, accompanied by changes in family roles, strengthened independence, and increased self-efficacy. The study also specifically found that social support and new responsibilities were important factors in accelerating recovery. Thus, resilience in emerging adults after the death of a sibling emerges through the interaction of emotional processing, meaning construction, and environmental support that strengthen future orientation.